The Mediatization of Religion: A Netnographic Study of Habib Husein Ja’far’s Da’wah on YouTube - Ellya Pratiwi (Jurnal Komunikasi Islam, 2024)
This study aims to examine how the mediatization of religion takes place in Habib Husein Ja’far’s da’wah through YouTube channel Jeda Nulis. Based on the framework of mediatization theory, religion is increasingly being incorporated into the logic of media. This study used a qualitative approch with the netnographic method. The findings show that the mediatization process of da'wah on YouTube Jeda Nulis occurs through adjustments to the da'wah method and its content format. Habib Ja’far displays a millennial persona and carries topics based on trends in society as his da'wah method approach. His da'wah is formed in popular content formats such as vlogs, podcasts, and talk shows. He also collaborated with popular figures who played an important role in increasing the engagement rate. From the perspective of the audience, the content of Jeda Nulis builds narratives about representing peaceful Islam and strengthening tolerance. At this phase, mediatization shows the potential transformation of da'wah in the digital era. At the same time, the mediatization of da'wah facilitates religious expressions which have implications for the emergence of hate speech in the digital space.